Green human resource management practices and millennial employees' retention in small and medium enterprises: The moderating impact of creativity climate from a developing country perspective - Islam, Md Asadul; Mendy, John; Haque, A. K. M. Ahasanul; Rahman, Mahfuzur (Wiley-Blackwell, 2022)
Drawing on social exchange theory (SET), this paper examines the gap in the application of green human resource management practices and its effectiveness on millennial employees' retention. This study employed quantitative analysis based on surveys using a sample of 389 respondents from different small and medium enterprises (SMEs) located in the Dhaka Division of Bangladesh. The results show a posi tive relationship between green training and development and green reward and millennial employees' retention. However, the results show a negative relationship between green recruitment and selection, green involvement, green performance management and millennial employees' retention. Additionally, we found that applying green training and development and green reward are most beneficial both individually and organisationally. This study's contribution to SET is referred to as ‘green creativity climate’ as we have found it to be a significant moderator that helps business leaders and HR practitioners understand which green practices are most effective in retaining the services of an elusive part of the workforce such as millennial employees. Our proposed model highlights how a green creativity climate can foster a new social exchange bond between SMEs and millennials and thereby mitigate against the resource difficulties and performance deficits partly triggered by millen nial turnovers.